Metabolomic Applications in Animal Science - Tomonaga, Shozo (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Metabolomics has been a useful method for various study fields. However, its application in animal science does not seem to be sufficient. Metabolomics will be useful for various studies in animal science: Animal genetics and breeding, animal physiology, animal nutrition, animal products (milk, meat, eggs, and their by-products) and their processing, livestock environment, animal biotechnology, animal behavior, and animal welfare. More application examples and protocols for animal science will promote more motivation to use metabolomics effectively in the study field. Therefore, in this Special Issue, we introduced some research and review articles for "Metabolomic Applications in Anmal Science". The main methods used were mass spectrometry or nuclear magnetic resonance spectroscopy. Not only a non-targeted, but also a targeted, analysis of metabolites is shown. The topics include dietary and pharmacological interventions and protocols for metabolomic experiments.